Fabrication and Analysis of Amorphous Silicon TFT - Srikanth G; Yadhuraj S R; Subramanyam T K; Satheesh Babu Gandla; Uma B V (Institute of Advanced Engineering and Science, 2017)
The display technology and large area electronics got momentum with the introduction of TFT devices. TFTs can be made using different semiconducting materials or organic conducting materials as the active layer. Each one of them differ in their performance depending on the material used for the active layer. In this paper, fabrication of amorphous silicon TFT using PECVD is carried out. Simulation of the a-Si: H TFT is also carried out with the dimensions similar to that of the masks used for the fabrication. The Id-Vd plot for both the simulation and fabrication is obtained and studied.